Associations of HIV persistence, cigarette smoking, inflammation, and pulmonary dysfunction in people with HIV on antiretroviral therapy. Issue 27 (8th July 2022) - Cyktor, Joshua; Qin, Shulin; Staines, Brittany; Nouraie, Mehdi; Fitzpatrick, Meghan; Kessinger, Cathy; DeSensi, Rebecca; Huang, Laurence; Rinaldo, Charles R.; Kingsley, Lawrence; Tien, Phyllis C.; Mellors, John W.; et al.
Abstract : We aimed to investigate the relationship between measures of HIV persistence with antiretroviral therapy (ART) and cigarette smoking, systemic markers of inflammation, and pulmonary function. Retrospective study of 82 people with HIV (PWH) on ART for a median of 6.9 years (5.6–7.8) and plasma HIV RNA levels <50 copies/mL. HIV DNA and cell-associated HIV RNA (CA-RNA) were measured in peripheral blood mononuclear cells (PBMC) and plasma HIV RNA was measured by single-copy assay (SCA). Plasma levels of 17 inflammatory mediators were measured by Bio-Plex, and standard pulmonary function tests (PFT) were performed in all participants. Median age was 52 years and 41% were women. Most had preserved CD4 + T cell counts (median (IQR) 580 (361–895) cells/mm 3 ). Median plasma HIV RNA was 1.3 (0.7–4.6) copies/mL, and median levels of HIV DNA and CA-RNA in PBMC were 346 (140–541) copies and 19 (3.7–49) copies per 1 million PBMC, respectively. HIV DNA was higher in smokers than in nonsmokers ( R = 0.3, P < 0.05), and smoking pack-years positively correlated with HIV DNA and CA-RNA ( R = 0.3, P < 0.05 and R = 0.4, P < 0.01, respectively). HIV DNA, CA-RNA, and plasma HIV RNA were not significantly associated with any measure of pulmonary function or inflammation. Cigarette smoking was associated with HIV DNA and CA-RNA levels in blood, but measures of HIV persistence were not associated with pulmonary function or inflammation.